Um estudo dos pronomes indefinidos sob a ótica das operações enunciativas - Rasteiro, Cléia Janier Rodrigues [UNESP] (2014)
This research aims to build a relation between linguistic analysis and learning-teaching practices of mother language. This work takes as reference the theoretical and methodological model provided by the French linguist Antoine Cullioli in his Predicative and Enunciative Operations Theory (TOPE). Our investigation has as main objective to observe, analyse and understand how the students use the indefinite pronouns somebody/someone (alguém), nobody/no one (ninguém), no/any (nenhum) and some/any (algum) in written texts of different genres and in oral enunciations. We consider observations of application of indefinite pronouns used by students and we compare and contrast how the students understand these pronouns and how normative, functional and descriptive grammars define and classify them. However, the grammars we deal with in schools, mainly normative grammar, have extremely classificatory nature, because as much as those grammars seek variation and displacement of grammatical classes, they still have as units of study the static structures of the language. In addition to the main objective, other objectives on which our research is based are: determining the semantic and syntactic notions exercised by such pronouns in the fragments of texts produced by them; lead the student to reflect on building their linguistic process; guide the student to understand that the disambiguation process occurs at every moment within a range of paraphrase families; during the variation process, guide the student to understand that a notion only stabilizes at the time when the utterance occurs, and finally to identify the absence of reflection on the traditional activities of interpretation of texts, grammar and lexicon. To obtain the job corpus, activities were developed with two 8th/9th grade classes of Ensino Fundamental II (junior high school), at the public school EE Prof.ª Lea Monteiro de Freitas (Araraquara /SP) between February and...